Instilling the Value of Mutual Cooperation in Civics Education through Regular Collective Waste Disposal Activities as a Strategy for Environmental Damage Prevention among Elementary School Students - Syaibatul Aslamiah; Mirna Astuti; Wahyu Hidayat (International Journal of Basic Educational Research, 2026)
The natural environment is closely interconnected with human life, making environmental awareness and responsibility essential to ensure sustainability. One of the current challenges in education is the decline of students’ environmental awareness as a result of moral degradation, particularly reflected in the habit of littering. This study aims to describe the implementation of routine waste disposal activities through habituation of gotong royong (mutual cooperation) as an effort to develop environmental care character among students at SDN 2 Pemangkih Seberang. This research employed a qualitative method with a case study approach. Data were collected through direct observation, documentation, and interviews with the school principal. The collected data were analyzed descriptively to portray the process and outcomes of the habituation activities. The results indicate that routine gotong royong activities carried out three times a week effectively foster positive habits among students, including discipline, responsibility, cooperation, and environmental awareness. Furthermore, this habituation process successfully internalizes character values integrated into Civic Education learning, particularly within the gotong royong material. Therefore, routine waste disposal activities through gotong royong habituation can serve as an effective strategy for instilling environmental care character and shaping students with noble character and responsibility toward their surrounding environment.